Study Of The Effectiveness Of Drip Irrigation Techniques On The Use Of Diferent Mulse In Dry Land Tomato Cultivation - Lilis Permatasari; Muliatiningsih Muliatiningsih; Muanah Muanah (Universitas Muhammadiyah Mataram, 2021)
In order to meet the water needs of tomato plants and ensure that they grow well, an adequate irrigation water supply systems that are ideal for tomato plans. This analysis aims to 1] determine the effectiveness of drip irrigation techniques on tomato plant growth on dry land, and 2] assess the impact of drip irrigation techniques on plots given silver and straw plastic mulch, as well as properties without both. This research used an experimental apporoach that included both field and laboratory experiments. A one-factor randomized blog design (RBD) was used in this analysis, with three treatments: P1 = no mulch and straw, P2 = silver color plastic mulch, and P3= straw. The least significant difference method (LSD) was evaluated at the 5% actual level using SPSS analysis. Observation data were analyzed using two apporoaches: a mathematical apporoach using Microsoft excel and statical analysis using ANOVA analysis. The serults showed that the parameters of plant height, stem diameter, and the number of leaves of tomato plants had a significant impact on P1 ( no mulch and straw), P2 ( Silver Color Plastic Mulch), and P3 (Silverr Color Plastic mulch) (straw). It applied drip irrigation techniques to the growth of tomato plants in dryland. Although tomato plant wet weight and tomato plant dry weight parameters had a significant impact on tomato plant growth and dry weight than P1 and P3. It results in an average wet weight of 162.678 grams, P1 24.05 grams, P3 81.10 grams, and an average dry weight of 31.62 grams, P1 5.84 grams P3 18.74 gram, respectively.